Hard training for 5 mo increases Na(+)-K+ pump concentration in skeletal muscle of cross-country skiers - Evertsen, F.; Medbo, J. I.; Jebens, E.; Nicolaysen, K. (American Journal of Physiology, Endocrinology and Metabolism, 1997)
To study how training affects the Na(+)-K+ pump concentration, 11 male and 9 female elite junior cross-country skiers trained 12-15 h/wk at 60-70% (moderate-intensity group) or 80-90% (high-intensity group) of their maximal O2 uptake for 5 mo. Muscle biopsies taken from the vastus lateralis muscle before and after the training period were analyzed for Na(+)-K+ pump concentration by the [3H]ouabain-binding technique. Before training, the concentration was 343 +/- 11 nmol/kg wet muscle mass (mean +/- SE) for the men and 281 +/- 14 nmol/kg for the women (18% less than for the men, P = 0.003). The Na(+)-K+ pump concentration rose by 49 +/- 11 nmol/kg (16%, P < 0.001) for all subjects pooled during the training period, and there was no difference between the two training groups (P = 0.3) or the sexes (P = 0.5) in this increase. The Na(+)-K+ pump concentration correlated with the maximal O2 uptake (r = 0.6, P = 0.003), with the performance during a 20-min treadmill run (r = 0.6, P = 0.003), and to the rank of the subjects' performance as cross-country skiers (Spearman's rank correlation coefficient = 0.76, P < 0.001). These data could mean that for elite cross-country skiers the performance is related to the Na(+)-K+ pump concentration. However, other studies have shown an equally high pump concentration for far less fit subjects, suggesting that the pump concentration may not be a limiting factor.